2022
DOI: 10.1111/jfpp.16338
|View full text |Cite
|
Sign up to set email alerts
|

UV‐C irradiation delays browning of fresh‐cut “Fuji” apples

Abstract: In order to explore the effect and the corresponding physiological mechanisms of UV-C irradiation on browning of fresh-cut apples, both whole and sliced apple were irradiated with UV-C (254 nm) for 5 min before or after processing. The browning index (BI) of slices was immediately measured, while other relevant physiological parameters were evaluated on quick-frozen samples during refrigerated storage. Results indicated that both pre-and post-processing UV-C treatments effectively delayed browning of apple sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Similar behavior has been also reported in minimally processed yam slices (Li et al, 2016) and fresh‐cut Chinese yams (Luo et al, 2015). On the other hand, Yuan et al (2022) observed an increase in PPO activity and a reduction in browning with the application of UV‐C in fresh‐cut apples, indicating that the factor that limited the color change was the phenol content. Therefore, it could be deduced that the effect of UV‐C on the enzymatic browning prevention mechanism varies depending on the vegetal and the dose used, as indicated by Gutiérrez et al (2018) and Yuan et al (2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar behavior has been also reported in minimally processed yam slices (Li et al, 2016) and fresh‐cut Chinese yams (Luo et al, 2015). On the other hand, Yuan et al (2022) observed an increase in PPO activity and a reduction in browning with the application of UV‐C in fresh‐cut apples, indicating that the factor that limited the color change was the phenol content. Therefore, it could be deduced that the effect of UV‐C on the enzymatic browning prevention mechanism varies depending on the vegetal and the dose used, as indicated by Gutiérrez et al (2018) and Yuan et al (2022).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Yuan et al (2022) observed an increase in PPO activity and a reduction in browning with the application of UV‐C in fresh‐cut apples, indicating that the factor that limited the color change was the phenol content. Therefore, it could be deduced that the effect of UV‐C on the enzymatic browning prevention mechanism varies depending on the vegetal and the dose used, as indicated by Gutiérrez et al (2018) and Yuan et al (2022). These results indicate that exposure to a dose of 1 kJ/m 2 of UV‐C could modulate a signaling pathway that is beneficial for the vegetable since it involves an attenuated activity of the PPO enzyme and preservation of the levels of phenolic compounds and ascorbic acid content.…”
Section: Resultsmentioning
confidence: 99%
“…MDA content was measured referred to Yuan et al . (2022). The pulp (1 g) and trichloroacetic (TCA, 100 g L −1 , 5 mL) were homogenised and centrifuged at 10 000 g at 4 °C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a study investigated the effect of UV‐C treatment at 254 nm for 5 min on browning inhibition of Fuji fresh‐cut (Yuan et al., 2022). The treatment was conducted before or after processing (cutting, coring, peeling).…”
Section: Inhibition Of Enzymatic Browningmentioning
confidence: 99%
“…The PPO activity of apple treated either before or after processing was lower than control after 8 days of storage at 4°C, while in contrast, it was higher than control before 8 days of storage. UV‐C treatment reduced H 2 O 2 accumulation and TPC, but the antioxidant activity (2,2′‐Azino‐bis(3‐ethylbenzthiazoline‐6‐sulfonic acid) or ABTS) of treated apple was higher than control, especially up to 6 days of storage (Yuan et al., 2022). Another study used the same wavelength of UV‐C treatment, but could not find a significant PPO inhibition in Gala juice, even at 53 kJ/L (Müller et al., 2013).…”
Section: Inhibition Of Enzymatic Browningmentioning
confidence: 99%